Fractional creep model and experimental study of unsaturated silty clay in Fuyang - Wu, Daguo; Chen, Guangyao; Xia, Zhenzhao; Peng, Jianhe; Mao, Jingyin (Frontiers in Earth Science, 2023)
Due to the long-term overdraft of groundwater in Fuyang, silty clay in this area has been in an unsaturated state for a long time, which caused ground subsidence and threatened the safety of engineering construction. Creep is an important part of ground subsidence, but it is easily ignored in ground subsidence caused by groundwater overdraft. Therefore, in order to explore the creep behavior in this environment, a series of triaxial creep tests of unsaturated soil were conducted to research the effects of deviator stress, matrix suction and net confining pressure on creep. Then, based on analysis results of the geometric characteristics of the test creep curves, an improved fractional order Nishihara model of unsaturated soil under triaxial stress conditions was constructed by using fractional calculus theory. Finally, the effectiveness of improved fractional order Nishihara model was verified based on cooperation search algorithm and minimum mean square error principle. The simulation results show that the fitting curves of improved fractional order Nishihara model are in good agreement with the test curves, and it is feasible and effective to describe the creep characteristics of unsaturated silty clay in Fuyang.